Bioinorganic Relevance of Some Cobalt(II) Complexes with Thiophene-2-glyoxal Derived Schiff Bases - Prashant Singh; Shanu Das; Rajesh Dhakarey (E-Journal of Chemistry)
Complexes of Co(II) with two new Schiff bases TEAB [2-hydroxy-4-{[2-oxo-2-(thiophen-2-yl)ethylidene]amino}benzoic acid] and TEPC [N-[2-oxo-2-(thiophen-2-yl)ethylidene]pyridine-3-carboxamide] have been synthesized and characterized with the help of elemental analysis, magnetic, mass, 1H-NMR, 13C-NMR, IR and electronic spectral data. IR spectra manifest the coordination of the ligand to the metal ion through the carbonyl oxygen, azomethine nitrogen and thienyl sulphur atoms. With the help of electronic spectral data various ligand field parameters were also calculated. All these studies reveal the distorted octahedral Co(II) complexes. Synthesized compounds have also been screened against some micro organisms viz, Escherichia coli, Proteus vulgaris, Aspergillus niger and Aspergillus flavus with the help of ‘filter paper disc’ technique. It has been observed that the antimicrobial activities of metal complexes are higher than that of the free ligand.